Neural Tube Defects in Embryonic Life: Lessons Learned From 340 Early Pregnancy Failures. (17th April 2018) - Hartge, David R.; Gembicki, Michael; Rody, Achim; Weichert, Jan
Abstract : Objectives: The aim of this study was to evaluate the feasibility of sonographic assessment of the embryonic/fetal neural tube in nonviable pregnancies and to determine the defect incidence. Methods: Prospective analysis of transvaginally acquired 3‐dimensional (3D) multiplanar and 3D surface‐rendered volume sets of 340 cases of missed abortion between March 2010 and September 2015 was performed. Data regarding karyotype and postmortem examination as well as demographic features and the outcomes of subsequent pregnancies were evaluated. Results: In 223 cases, an embryo/fetus was detected and considered suitable for further evaluation: in 37 of 223 (16.6%) embryos/fetuses, a neural tube defect was present: 27 of 37 cephaloceles, 5 of 37 anencephalies/exencepahlies, 3 of 37 spina bifidas, 1 of 37 caudal regression syndrome, and 1 of 37 iniencephaly. Additional alterations were not observed. In 7 of 37 cases karyotyping was carried out and showed no aneuploidy. Eight subsequent pregnancies had a favorable outcome, with 1 ending in an intrauterine fetal death during the 22nd week of gestation. Maternal folic acid supplementation was provided for all subsequent pregnancies. No neural tube defects occurred. Conclusions: Sonographic 3D evaluation of complete neural tube closure in embryonic/fetal demise is technically feasible and can be achieved in embryos with a crown‐rump length greater than 8 mm. In 26 of 37 cases a defective closure site could be allocated to high‐risk areas known for early embryonic demise. Regardless of the etiology of different neural tube defects, high‐dose folic acid prophylaxis must be recommended in all cases. Sonographic evaluation of the neural tube, including 3D surface‐rendered images, should be offered to every woman with a missed abortion because of the impact on subsequent pregnancies.